COMPARATIVE EFFICACY OF DENTAL LASERS VERSUS MOUTHWASH IN ROOT CANAL DISINFECTION - Mousa Yahia Karyri; Abdulaziz Marzouq Alghawazi; Sarra Mohsen Al-Otaibi; Ahad Alhumaidi Almutairi; Mohammed Ahmed Algarni; Turki Farhan Omish Alharbi; Rami Amin Gashgary; Ali Mohammed A Aldossari (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Introduction: In the realm of endodontic treatment, innovative laser technologies are emerging as promising alternatives to traditional chemo-mechanical methods for root canal disinfection. These laser techniques are reputed to penetrate deeper into dentin, offering enhanced bacterial eradication. This systematic review seeks to explore the efficacy of dental lasers in purifying root canals during endodontic procedures. Methods: This review was conducted through a comprehensive search on PubMed and Medline, employing a series of specific keywords. The search was confined to articles published in English. Additionally, references from relevant articles were scrutinized for inclusion. The studies selected for review spanned a range of wavelengths from 600 to 2940 nm across the electromagnetic spectrum, encompassing technologies such as LED, halogen lamps, Nd:YAG, Er, Cr:YSGG, Er:YAG, and quartz tungsten halogen with blue light laser. Results: From the 254 articles initially identified, nine met the inclusion criteria for this systematic review. A common limitation among these studies was the lack of justification for the sample size, with no power analysis reported. Furthermore, none of the studies implemented blinding during either the treatment or the outcome evaluation phases. The review noted significant heterogeneity in the application of the laser treatments. Conclusions: The findings indicate that dental lasers are capable of significantly reducing bacterial populations within the root canal, though sodium hypochlorite remains superior in effectiveness. However, the laser’s ability to extend its antibacterial effects beyond 1mm into the dentin suggests its utility in sealing dentinal tubules and eradicating bacteria such as Escherichia coli and Enterococcus faecalis. Consequently, integrating laser treatment with conventional rinsing solutions is advocated for enhanced canal disinfection.